Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41541-023-00657-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects, perceptions and attitudes related to BNT162b2, mRNA-1273 or JNJ-78436735 SARS-CoV-2 vaccines: Population-based cohort

Abstract: Long-term control of SARS-CoV-2 requires effective vaccination strategies. This has been challenged by public mistrust and the spread of misinformation regarding vaccine safety. Better understanding and communication of the longer-term and comparative experiences of individuals in the general population following vaccination are required. In this population-based longitudinal study, we included 575 adults, randomly selected from all individuals presenting to a Swiss reference vaccination center, for receipt of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Our failure time analyses depicted a dichotomy of participants who did not use the SwissCovid app and did not get vaccinated (16% of pooled study population) versus participants who used the app and got vaccinated (40% of pooled study population) during the study period. The persistent divergence of these two groups over the study period suggests a continued low acceptance of public health measures in reducing viral transmission, such as from the observed negative discourse on the implementation of COVID-19 vaccine certificate in June 2021 [46][47][48][49]. On the other hand, we observed that the majority of SwissCovid app users at baseline (approximately 50% of pooled study population) continued using the app and got vaccinated during the study period.…”
Section: Discussionmentioning
confidence: 72%
“…Our failure time analyses depicted a dichotomy of participants who did not use the SwissCovid app and did not get vaccinated (16% of pooled study population) versus participants who used the app and got vaccinated (40% of pooled study population) during the study period. The persistent divergence of these two groups over the study period suggests a continued low acceptance of public health measures in reducing viral transmission, such as from the observed negative discourse on the implementation of COVID-19 vaccine certificate in June 2021 [46][47][48][49]. On the other hand, we observed that the majority of SwissCovid app users at baseline (approximately 50% of pooled study population) continued using the app and got vaccinated during the study period.…”
Section: Discussionmentioning
confidence: 72%